A systematic review and meta-analysis of lifestyle and body mass index predictors of successful assisted reproductive technologies - Satvinder Purewal; S. C. E. Chapman; O. B. A van den Akker (Taylor & Francis Group, 2019)
Objective: Lifestyle (smoking, drinking alcohol) and body mass index (BMI) predictors of successful outcomes in assisted reproductive technology (ART) treatments were examined in this meta-analysis. Method: A bibliographic search was undertaken using six databases. The review was informed by PRISMA/MOOSE guidelines. Meta-analytic data were analysed using random effects models. Results: We included 77 studies examining effects of BMI, smoking and drinking alcohol. Patients with a BMI< =24.9 were significantly more likely to achieve LB/pregnancy than with BMI> =25 OR = 1.219 (95% CI:1.128-1.319, z = 4.971, p < .001; I2 = 53.779%, p = .001). Non-smokers were significantly more likely to achieve a LB or pregnancy than smokers OR = 1.457 (95% CI:1.228-1.727, z = 4.324, p < .001; I2 = 51.883; p = .001). Meta-regression revealed the number of embryos transferred significantly moderated the effects of smoking on ART outcomes, and there was a trend indicating primary infertility and high BMI were also significant moderators. The evidence for drinking alcohol was inconclusive due to the small number of studies. Conclusions: This meta-analysis confirms that ART treatment success can be predicted with lifestyle factors. Further, non-smokers' relative odds of pregnancy/live birth increase as more embryos were transferred but there was a trend that the odds of pregnancy/live birth decrease with primary infertility and high BMI.